Embarking on the sustainable journey with corporate governance - Chai, Ker Li; Choi, Kee Fong; Keu, Lian Wen; Khoo, Wei Chin; Loo, Lily (2023)
This research is aimed to investigate the relationship between corporate governance and sustainability of conventional banks among six ASEAN countries. The study examines the effect of corporate governance on sustainability by including the independent variables of CEO power, board structure, audit, firm control and economic. This research project's target sample consists of conventional banks within ASEAN countries which are Malaysia, Singapore, Vietnam, Indonesia, Philippines, and Thailand with a total number of 440 observations. Data from 2014 to 2021 are collected and analysed through various tests using STATA. The research project concluded that the independent variable has a significant impact on economic sustainability, followed by social sustainability, while environmental sustainability has no strong direct relationship with the independent variable. The study includes several limitations and suggestions to give better ideas for future studies and even conventional banks in ASEAN to improve the sustainability development goal and corporate governance framework.